(untitled) (Journal of Surgical Sciences, 2019)
Inguinal hernias are common and the results of surgical repair are often satisfactory but recurrence rate are variable. To prevent recurrences prosthetic materials have been increasingly used in hernia repair. In this study Lichtenstein technique of tension free mesh repair for inguinal hernia is done in 275 cases in the period from January 2005 to Deceber2010 and outcome is measured in terms of early and late morbidity especially recurrences. serorna developed in 10 patients (3.6%) and haematoma and transient testicular swelling developed in 8 patients (2.9%) and 21 patients (7.6%) respectively. Only 3 patients (1.08%) developed wound infection and 2 patients (.72%) developed recurrences of hernia. Post operative neuralgia developed in 7 cases (2.5%). During follow up period no mesh rejection and discharging wound sinus related to presence of foreign body is observed in the study. So Lichtenstein tension free repair of inguinal hernia is. safe and effective method where recurrence rate is reasonably low. Journal of Surgical Sciences (2013) Vol. 17 (1) : 3-6